If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3j + 4 + -1j = 5j + -10 + -1j Reorder the terms: 4 + 3j + -1j = 5j + -10 + -1j Combine like terms: 3j + -1j = 2j 4 + 2j = 5j + -10 + -1j Reorder the terms: 4 + 2j = -10 + 5j + -1j Combine like terms: 5j + -1j = 4j 4 + 2j = -10 + 4j Solving 4 + 2j = -10 + 4j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-4j' to each side of the equation. 4 + 2j + -4j = -10 + 4j + -4j Combine like terms: 2j + -4j = -2j 4 + -2j = -10 + 4j + -4j Combine like terms: 4j + -4j = 0 4 + -2j = -10 + 0 4 + -2j = -10 Add '-4' to each side of the equation. 4 + -4 + -2j = -10 + -4 Combine like terms: 4 + -4 = 0 0 + -2j = -10 + -4 -2j = -10 + -4 Combine like terms: -10 + -4 = -14 -2j = -14 Divide each side by '-2'. j = 7 Simplifying j = 7
| 3(x•2)=96/2 | | X+40+106=180 | | 1-3x+4=-1-2c | | 9d-8=83 | | 2-0.8(2k-7)=1.2(k+1) | | (4-5x)/2=7 | | 1200=40x+20(1.5x) | | -2x+12=8x-8x | | 3(y-9)=12 | | d=5x+5y | | 35+.5x=20-.9x | | 8y-7=10y+11 | | 3x-100=3x+70 | | -61-11x=17-8x | | (-4x/6)-(-x-3) | | (-3a^3b)(-2b^4)(-a^4b^3)=equation | | (X^2)-(10x)+17=-4 | | -4m-13=3m+3-5m | | 16x^2+368x-2035=0 | | 3-8[3-(2y-9)]= | | -3.8+(-5.6)= | | 9÷3/5 | | 3.2=9 | | 15600=(200-10x)(90+5x) | | 5(v-6)=-2v+2 | | 2x+2y+2z=110 | | 35x=25+30x | | 33+8-x=180 | | 5(3-2)=-55 | | M-5=4m+13 | | 5(p+8)=85 | | -16.53=x-3.2 |